Kepuasan Kerja dan Motivasi Kerja terhadap Komitmen Organisasi Karyawan - Yusuf Fadhilah; Mei Retno Adiwati (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of job satisfaction and work motivation on the organizational commitment of employees of PT. Mahakam Kencana Intan Padi Surabaya. The research method used is quantitative. The population in this study were all employees of PT. Mahakam Kencana Intan Padi Surabaya with 38 employees. The sampling technique uses saturated sampling method. Data collection was carried out by distributing questionnaires, while data analysis techniques used SEM PLS with Smart PLS software. The results showed that job satisfaction and work motivation had a positive and significant effect on organizational commitment among employees at PT. Mahakam Kencana Intan Padi Surabaya. In conclusion, the presence of job satisfaction and good work motivation will create a strong organizational commitment to each employee. Keywords: Job Satisfaction, Organizational Commitment, Work Motivation